Rekomendasi Peminatan SMA Bagi Siswa Kelas IX SMP Menggunakan Metode AHP dan SMART - Sari Narulita Hantari; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Education has an important role in human life. Choosing the right education will have a positive impact on their future career. Based on Indonesian Education Curriculum starting from year 2013, high school major was carried out since 10th grade, at the time when new student admission is conducted. These changes have an impact on Junior High School students, who have to prepare to choose which major they they want to be in. Academic report, student interest, family's wealth, school they want to enroll, and parent's wishes are some factor that need to be considered. This study is conducted to make recommendation for 9th grade students in which major are suitable for them. The method used is Analytic Hierarcy Process (AHP) and Simple Multi Attribute Rating Technique (SMART). Criterias that being used is their study report, and their interest. AHP is used to calculate the weight of criteria, while SMART is used to determine recommendation result between IPA and IPS. Data testing is calculated 10 times using Spearman Correlation resulting in Ï=0.83458. The Spearman value (Ï) then compared to significance test table, resulting significant relationship between IPA and IPS.